The relevance of the magazine and reader relationship in the 21st century - Hermie, Patrick (Henry Stewart Talks, 2009)
Will digital ultimately kill print?, The challenge of media convergence, New opportunities and business models emerge, The reasons for reading digital, What do advertisers need?, The consumer has changed, Be part of the conversation, People have a positive attitude towards advertising in magazines, Magazines stand out as the medium people turn to for personalized information and ideas, Magazine brands and their fans form communities
Archived at 2022/11/27